2018
DOI: 10.1097/md.0000000000013332
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic polymorphism of methylenetetrahydrofolate reductase in a large ethnic Hakka population in southern China

Abstract: Methylenetetrahydrofolate reductase (MTHFR) catalyzes conversion of methylene tetrahydrofolate to methylte trahydrofolate. MTHFR C677T polymorphism has been regarded as a risk factor for various vascular diseases. Our study aimed to investigate the distribution frequencies of this polymorphism among Hakka population living in southern China. We retrospectively recruited 5102 unrelated Chinese Hakka subjects. MTHFR C677T polymorphism was tested using the polymerase chain reaction (PCR) and DNA sequencing. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The results indicated that 19.59% of individuals were wild-type homozygous (CC), 49.95% were heterozygous (CT), and the remaining individuals (30.46%) were mutant allele homozygous (TT). Previous studies on MTHFR gene polymorphism have shown considerable heterogeneity between different countries, and similar results have been observed in the Chinese population [ 2 , 3 ]. This present study showed that in north China the distribution of TT genotype in Shanxi was similar to that in Tianjin (30.4%) and Shaanxi (30.4%), lower than that in Shandong (40.8%) and Henan (37.0%), and higher than that in some of China's southern provinces such as Jiangsu (19.7%), Hubei (16.8%), Sichuan (13.8%), Yunnan (15.3%), Guangdong (8.3%), and Hainan (6.4%) [ 12 ].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The results indicated that 19.59% of individuals were wild-type homozygous (CC), 49.95% were heterozygous (CT), and the remaining individuals (30.46%) were mutant allele homozygous (TT). Previous studies on MTHFR gene polymorphism have shown considerable heterogeneity between different countries, and similar results have been observed in the Chinese population [ 2 , 3 ]. This present study showed that in north China the distribution of TT genotype in Shanxi was similar to that in Tianjin (30.4%) and Shaanxi (30.4%), lower than that in Shandong (40.8%) and Henan (37.0%), and higher than that in some of China's southern provinces such as Jiangsu (19.7%), Hubei (16.8%), Sichuan (13.8%), Yunnan (15.3%), Guangdong (8.3%), and Hainan (6.4%) [ 12 ].…”
Section: Discussionsupporting
confidence: 70%
“…It has been reported that the distribution of T alleles is the highest amongst the European population (24.5%–43.8%), followed by the Asian population (2.5%–36%) and African population (4.9%–9.1%) [ 2 ]. In terms of ethnic distribution, a previous study confirmed the differences in MTHFR C677T gene polymorphisms amongst 9 ethnic groups in China [ 3 ]. In the present study, the frequency of C677TT homozygous mutant genotypes in different provinces of China was investigated.…”
Section: Introductionmentioning
confidence: 65%
“…Previous studies have shown that there are more than 40 sites of polymorphism in MTHFR (10) , of which C677T and A1298C are the most important (11) . Compared with 677CC genotype, 677TT genotype performances about 34% MTHFR activity, while heterozygote 677CT shows about 65% MTHFR activity (12) .…”
Section: Introductionmentioning
confidence: 90%
“…[ 4 , 5 , 21 ] Moreover, the MTHFR 677C>T polymorphism is a commonly known heritable risk factor for elevated blood Hcy levels. [ 22 ] However, the T allele frequency of MTHFR 677C>T is highly variable throughout the world, with frequencies as high as 64.3% in Europeans and low frequencies of 4.9% to 9.1% among African populations. [ 23 , 24 ] In this study, we conducted the genotyping of 3378 perinatal women as a means of detecting the frequency of the MTHFR 677C>T polymorphism in this population (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%